PD-1/PD-L1 immune checkpoint inhibitors in glioblastoma: clinical studies, challenges and potential - Tianrui Yang; Ziren Kong; Wenbin Ma (Taylor & Francis Group, 2021)
Immune checkpoint inhibitors (CIs) have changed the landscape of tumor immunotherapy. Glioblastoma (GBM) remains the most common primary malignant brain tumor in adults and has a very poor prognosis. Due to the high invasiveness and aggressiveness of GBM, there is considerable interest in programmed cell death-1 (PD-1)/programmed cell death ligand-1 (PD-L1) treatment. However, the immunosuppressive and immune-privileged characteristics of GBM limit the efficacy of CIs. While clinical studies of CI monotherapies have shown unsatisfactory survival benefits, new treatment strategies have received attention. Multiple clinical studies have focused on combination of standard therapy (temozolomide, radiotherapy), targeted therapy and other immunotherapies, and some have reported results. Here, we reviewed recent clinical trials of anti-PD-1/PD-L1 monotherapy, studies with neoadjuvant strategies, and preclinical and clinical studies of combination immunotherapies for GBM. The preliminary clinical reports in certain subsets of patients with hypermutated or mismatch repair system deficiency GBM are also discussed.